"Sorry, I'm not a dentist": perspectives of rural GPs on oral health in the bush. Issue 1 (18th January 2016) - Barnett, Tony; Hoang, Ha; Stuart, Jackie; Crocombe, Leonard
Abstract: Objective: To examine the provision of oral health and oral health service in rural areas from the perspective of general practitioners working in communities without resident dentists. Design, setting and participants: A qualitative approach using face‐to‐face, semi‐structured interviews with 30 GPs from rural Queensland, Tasmania and South Australia, conducted between October 2013 and October 2014. Results: Four major themes emerged from the interviews: rural oral health, managing oral health presentations, barriers to patients seeing a dentist, and improving oral health. Rural GPs saw patients with a range of oral health problems, including toothache, abscesses and trauma, and observed poor oral health in their communities. Some acknowledged that they were not confident when dealing with oral health problems; they typically provided short‐term pain relief, prescriptions for antibiotics, and advised patients to see a dentist. Participants noted that rural patients may not see a dentist when advised to do so because symptoms had abated, oral health was regarded as a low priority, or the costs of travelling to and seeing a dentist discouraged them. The interviewees recommended building the capacity of GPs to better care for patients with oral health problems, establishing more effective communication and referral pathways between GPs and dentists, focusing on preventive dental care, and delivering dental services in more flexible and consistent ways that better meet the needs of the communities. Conclusions: Rural oral health could be improved by several approaches, including additional training for GPs in oral health care, primary prevention activities in communities, and improving the access to dental services.